Taco Bell : the breakfast opportunity - Calkins, Tim; Darrell, Blair ([London] : SAGE, 2016)
In 2013, Taco Bell was looking for ways to grow. One of the opportunities the company was considering was adding a line of breakfast foods, something the brand had tried - unsuccessfully - before. There were clear reasons to proceed with the launch, as breakfast offered a completely new meal occasion with tremendous potential. However, there were also notable concerns when it came to operational issues and consumer behavior. This case gives students an opportunity to debate growth and new product opportunities.
Originally Published in: Calkins, T., & Darrell, B. (2015). Taco Bell: The Breakfast Opportunity. 5-414-757. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Taco Bell (Firm); Brand name products -- Case studies; Fast food restaurants -- Management -- Case studies; Breakfasts -- Case studies; New products -- Marketing -- Case studies